Do Political Risks Influence Sharia Bank Stability? The Case of Southeast Asia - Zulfa Muasaroh Binti Rahmawati; Titis Miranti; Ulfi Kartika Oktaviana; Yenny Kornitasari (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The present study examines the influence of political risk on the stability of Sharia banks in Southeast Asia, a region characterized by rapid economic growth alongside significant political uncertainties. This study aims to fill a gap in the existing literature, which has largely focused on other regions like the Middle East and North Africa. This study employs a quantitative methodology, utilizing panel data regression with a Fixed Effects Model to analyze data from 17 of the largest Sharia banks in Southeast Asia over the period of 2018-2022. The data for the study were obtained from the annual financial reports of these banks. The key findings indicate that political risk has a significant negative impact on the stability of Sharia banks in the region. In contrast, the quality of regulation and the total assets of the banks were found to have a significant positive influence on their stability. Other internal factors, such as the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Return on Assets (ROA), did not show a statistically significant effect on bank stability in the context of this study. The results emphasize the importance for policymakers and regulators in Southeast Asian nations to actively manage political risks and continuously improve the quality of financial regulations to ensure the resilience of the Sharia banking sector. This research contributes valuable insights for academics, bankers, and government authorities by highlighting the crucial role of the political and regulatory environment in maintaining the stability of Islamic financial institutions.